Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Cooperative Learning Tipe Course Review Horay di Kelas V Sdn 03 Pulai Anak Air Kota Bukittinggi - Reza, Widya; Masniladevi, Masniladevi; Anita, Yesi; Fitria, Yanti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement of student learning outcomes in Pancasila Education learning through the application of the Cooperative Learning model of the Course Review Horay (CRH) type in grade V of SDN 03 Pulai Anak Air Bukittinggi. This study uses the Classroom Action Research (PTK) method with a qualitative and quantitative approach, carried out in two cycles that include the stages of planning, implementation, observation, and reflection. Data were collected through test and non-test techniques, with the research subjects consisting of teachers as observers, researchers as practitioners, and class V students. The results of the study showed an increase in several aspects: (1) Teaching modules increased from an average of 83.2% (B) in cycle I to 95.83% (SB) in cycle II; (2) The implementation of learning by teachers increased from 81.5% (B) to 95.45% (SB); (3) The implementation of student aspect learning increased from 81.5% (B) to 95.45% (SB); (4) Students' learning outcomes increased from an average of 76.69 (C) in cycle I to 90.53 (SB) in cycle II. In conclusion, the application of the Horay Course Review model has proven to be effective in improving student learning outcomes in Pancasila Education learning in grade V of SDN 03 Pulai Anak Air Bukittinggi